1990
DOI: 10.1097/00000658-199010000-00008
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Prostanoids in the Production of Acute Acalculous Cholecystitis by Platelet-activating Factor

Abstract: Gallbladder tissue from patients with acute acalculous cholecystitis contains increased amounts of prostanoids when compared to normal gallbladder tissue. Platelet-activating factor (PAF) is a potent stimulus of eicosanoid formation. It has been implicated as a mediator of acute inflammatory processes and systemic responses to shock. In this study the role of PAF in acute acalculous cholecystitis was evaluated. Anesthetized cats underwent gallbladder perfusion with a physiologic buffer solution containing [14C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0
1

Year Published

1991
1991
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(20 citation statements)
references
References 21 publications
3
16
0
1
Order By: Relevance
“…The incidence of 4 % in this study is comparable to that in other recent ICU series, which have reported an incidence ranging from 0.5 % to 5 % [3,7,13]. In our study selected patients showed a high incidence of various risk factors described in the literature, namely surgery, trauma [1,15], fasting, total parenteral nutrition [5,17], mechanical ventilation with PEEP [4,16], and narcotics analgesia [6], accounting for 43 % of patients with AAC among the patients suspected.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The incidence of 4 % in this study is comparable to that in other recent ICU series, which have reported an incidence ranging from 0.5 % to 5 % [3,7,13]. In our study selected patients showed a high incidence of various risk factors described in the literature, namely surgery, trauma [1,15], fasting, total parenteral nutrition [5,17], mechanical ventilation with PEEP [4,16], and narcotics analgesia [6], accounting for 43 % of patients with AAC among the patients suspected.…”
Section: Discussionsupporting
confidence: 87%
“…Each of these criteria had good sensitivity (90±100 %) but poor specificity (40±60 %) [15]. Combining the three major criteria reduces the sensitivity of US up to 40 % but increases its specificity up to 95 % [15,18]; this was confirmed by our results of 50 % sensitivity and 94 % specificity.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Literature 174 also highlights the importance of the humoral response to inflammatory mediator release, splanchnic ischemia and gram-negative bacteria to the pathogenesis of AAC. Lipopolysaccharide elicits a substantial host response by activating coagulation cascades and generating plateletactivating factors, which have been observed in pathogenesis in animal AAC models [23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…These patients represent a unique challenge, as most are gravely ill from other sources at the time of their initial presentation [35]. Although the pathogenesis of this uncommon syndrome is still unclear, such factors as local ischemia, oxygen radical formation, and inflammatory cytokine release appear to be involved [36]. A number of treatment options are available with the best choice dependent on the clinical status of the patient.…”
Section: Acute Acalculous Cholecystitismentioning
confidence: 99%